IN ENGLISH OR INTO ENGLISH? PREPOSITIONAL AND PARTICLE USAGE IN TRANSLATED DISCOURSE - Rodriguez-Murphy, Elena (2017)
On carrying out diagnostic assessment of the different levels of “interlanguage” (Selinker, 1972) of translator trainees at the University of Salamanca, who use their working languages—in this case English—at nearnative level when practising inverse translation, the writer has been able to observe that one of the areas in which even the most proficient students are likely to find certain difficulty is that of prepositional “usage” and “use” (Widdowson, 1978). When dealing with the interpretation and translation of prepositions and particles in a wide range of structures and contexts, knowledge of both their usage and a feeling for their use is essential if the often important nuances which they express in combination with other linguistic elements are not to be forfeited. The principal aim of this article is to underline this notion, contributing.both samples of prepositional and particle usage in translation and relevantobservations for promoting the in-class development of an awareness of theproblems encountered concerning the comprehension of the source text and itssubsequent re-expression.